2019
DOI: 10.1186/s12902-019-0459-z
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of adrenal crisis in steroid-dependent patients: causes, frequency and outcomes

Abstract: Background: Adrenal patients have a lifelong dependency on steroid replacement therapy and are vulnerable to sudden death from undertreated adrenal crisis. Urgent treatment with parenteral steroids is needed, often with IV saline for volume repletion. Episodes of adrenal crisis are, for most patients, relatively infrequent and they may not be well prepared to respond. This study explores how patients recall previous episodes of adrenal crisis and their satisfaction with UK emergency medical treatment. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
13
0
6
Order By: Relevance
“…One reason for this shortcoming might be insufficient knowledge of physicians of AI. Only less than 10 % of interviewed physicians identified all situations requiring glucocorticoid adjustment correctly [38,39]. Another reason might be the low recognition value of different emergency cards handed out to patients.…”
Section: Current Shortcomingsmentioning
confidence: 96%
See 1 more Smart Citation
“…One reason for this shortcoming might be insufficient knowledge of physicians of AI. Only less than 10 % of interviewed physicians identified all situations requiring glucocorticoid adjustment correctly [38,39]. Another reason might be the low recognition value of different emergency cards handed out to patients.…”
Section: Current Shortcomingsmentioning
confidence: 96%
“…Recent data from a prospective study showed that patients who performed a self-injection had an improved outcome: after initial parenteral (intramuscular or subcutaneous) glucocorticoid administration by patients or their relatives, significantly more patients were treated on an outpatient basis (62%) compared to patients who did not self-inject (27%), (p=0.008) 37 . Two surveys from 2013 and 2017/18 in British patients revealed that within a 5-year interval more patients performed self-injection for treatment of emergency situations (16.7% versus 24%) 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology is nonnegligible with 5 to 17 AC cases occurring per 100 patient-years in patients with primary or SAI. 132 The mortality rate is high, estimated between 0.5 and 2%. 133,134 Precipitating Factors Several factors can be involved in precipitating an AC, commonly including interruption of glucocorticoid intake, infections, surgery, gastroenteritis, and emotional or physical stress.…”
Section: Adrenal Crisismentioning
confidence: 99%
“…This issue is compounded by the closure of shops, stalls, and businesses and the implementation of a lockdown by the government. In steroid-dependent individuals, sudden cessation of these unregulated drugs may lead to adrenal insufficiency and eventually adrenal crisis, a life-threatening condition [6,7].…”
mentioning
confidence: 99%